Macan Ali: A symbol of Acculturation between Islam and Javanese Mysticism in Cirebon - Afifi Hasbunallah; JM Muslimin; Nida Dusturia (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This article explores the practice of symbolization, investigating how flags acquire specific characteristics that enable their use as symbols. The main objective of this study is to describe the Macan Ali flag, with a particular focus on its connection to mysticism and Islam within the context of Javanese culture, specifically in Cirebon. This study reveals that the Macan Ali, when viewed as a symbol, can be interpreted as a concept that manifests as an entity embodying logical-analytical qualities. A comprehensive understanding of the philosophy of symbols allows for the harmonious integration of literal and figurative meanings within the Macan Ali symbol. Furthermore, it plays a pivotal role in harmonizing the two distinct concepts of Javanese mysticism and Islam. This synthesis underscores the multifaceted nature of symbols and their capacity to bridge diverse cultural and religious paradigms.